EVALUASI PASCADIKLAT INDUSTRI PENGOLAHAN DAN PEMURNIAN MINERAL PPSDM GEOMINERBA TERHADAP PENINGKATAN KOMPETENSI ALUMNI PADA INDUSTRI SMELTER (LOKUS: SULAWESI TENGGARA) - Imelda Hutabarat; Revi Timora Salajar (PPSDM Geominerba, 2019)
The development of the processing and refining industry cannot be separated from the mandate of Law No. 4 of 2009 concerning Mineral and Coal Mining which requires domestically is obliged to process and refine minerals and coal in the country. There are still few schools that specialize in mining and metallurgy. Including high school (SMA) and vocational high school (SMK) still do not have a metallurgical curriculum. Thus there are competency gaps possessed by high school /vocational school students to enter metallurgical industries. Therefore, to reduce the competency gap possessed by high school / vocational school graduates in the locations around the smelter industry that are built, vocational training is needed to be able to provide the knowledge, skills and attitudes needed by high school/ vocational graduates to be accepted in the smelter industry. Post-Training Evaluation was carried out in Southeast Sulawesi province, where the rapid development of the smelter industry in this province. The results of the post-training evaluation specifically found that the practice time in the training was considered to be added. Even though it is quite a large amount of practice time allocated to education and training (50%), the skills provided are not too specific as those done in companies in South Sulawesi.